Animalities: Clues for an Alternative Map of Ethical, Political and Aesthetic Grammars in Latin American Cultures. Introduction - Adriana López-Labourdette; Magdalena López (Iberoamericana. América Latina - España - Portugal, 2020)
Introdution to the Dossier.